THE RELATIONSHIP OF THE COMMUNITY KNOWLEDGE LEVEL AMONG BEHAVIOR OF HANDLING NONCOROSIVE AGENT FOOD POINTING IN SINDANG BARANG BOGOR: HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT DENGAN PERILAKU PENANGANAN KERACUNAN MAKANAN NONCOROSIVE AGENT DI KELURAHAN SINDANG BARANG KOTA BOGOR - Tety Tety Novianty; Mulyani Siti Mulyani (Jurnal Ilmiah Wijaya, 2019)
Food includes for the most important and very essential basic needs in human life. Called food poisoning if someone experiences health problems after consuming food which contaminated with bacteria or poison which produced by bacteria diseases. These microorganisms can enter to our bodies through the food with people mediators who process food or indeed come from the food itself by poor processing result. Non-corrosive food poisoning is a food material that is not derived from chemicals containing corrosive substances. The purpose of the research was to determine the connection between the knowledge level of the society with the behavior of handling non corrosive food poisoning agent in Sindang Barang Bogor. The type of the research used is quantitative analysis with the research design using descriptive analytical method through cross sectional approach. The population in this study was 140 citizens in Sindang Bogor. The amount of sampling used in the assessment was using the Slovin formula. So the sample in this research was 60 respondents. The results showed that from the total of 60 respondents, 24 people (40.0%) had a good level of knowledge. The Non-Corrosive Food Poisoning Behavior results stated that of 60 respondents, 34 people (56.7%) had negative Non-corrosive food poisoning behavior. There is a significant connection between the knowledge level of the society with the behavior of handling non corrosive agent food poisoning in Sindang Barang Bogor with value p= 0,002(p value > α). It was expected that the society in Sindang Barang Bogor can handle food poisoning Non- corrosive agent from factors so that the incidence of Non-corrosive food poisoning can be overcome.